ASPEK HUKUM TATA KELOLA PERUSAHAAN YANG BAIK (GOOD CORPORATE GOVERNANCE) PADA PERSEROAN TERBATAS (STUDI PADA PT. ASIANTFAST MARINE INDUSTRIES) - Muhammad Ali Hakim (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
A company must provide adequate incentives for Commissioners and Directors to achieve company goals for the benefit of the company and its shareholders. By creating a system, Good Corporate Governance seeks to synergize through an ethics of the business world that is bound to certain rules that form the basis for adoption in the regulations, guidelines, and procedures that apply to carry out the operation of a company by implementing good corporate governance. GCG is a must in order to build strong and sustainable company conditions. The application of the concept is expected to be a more transparent company management for all interested parties. The problems formulated are 1. How to regulate the law of Good Corporate Governance at PT. Asianfast Marine Industries? 2. Has Good Corporate Governance at PT. Asianfast Marine Industries been carried out properly in accordance with the law?This type of research is a juridisnormative research, which is descriptive analytical. Data sources used in normative legal research are primary data and secondary data, with qualitative data analysis done deductively meaning using theories not only theory but also legal norms as tools, measures and even instruments to build hypotheses.The results of this study are that this research is focused on GCG in the context of Law Number 40 of 2007 concerning Limited Liability Companies and GCG guidelines issued by the National Committee on Governance policy which was approved by the Coordinating Minister for Economic Affairs of the Republic of Indonesia in 2006, in which PT. Asianfast Marine Industries makes a Good Corporate Governance Guidelines that follow the Guidelines issued by National Committee on Governance Policy which are the basis for implementing the implementation of GCG principles at PT. Asianfast Marine Industries.Keywords: Limited Liability Company, Principles, GCG